2006
DOI: 10.1111/j.1365-2443.2006.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin assembly factor 1 ensures the stable maintenance of silent chromatin states in Arabidopsis

Abstract: Newly synthesized DNA is rapidly assembled into mature nucleosomes by the deposition of preexisting and nascent histones, and some parts of this process are facilitated by chromatin assembly factor 1 (CAF-1). Loss-of-function mutants of CAF-1 in Arabidopsis , fasciata ( fas ), show a variety of morphological abnormalities and unique defects in gene expression in the meristems. In order to clarify the implications of CAF-1 in the maintenance of chromatin states in higher eukaryotes, we investigated transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
84
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 41 publications
1
84
1
1
Order By: Relevance
“…In addition, they showed that CAF-1 is dispensable for maintenance of DNA methylation. In another report, transcriptional silencing of the endogenous CACTA transposon is relieved in fas mutants (Ono et al, 2006), although this transcriptional activation was relatively weak, infrequent, and stochastic. We have found that transcriptional activation of a set of euchromatin genes is not due to global changes in chromatin organization over large chromosomal regions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they showed that CAF-1 is dispensable for maintenance of DNA methylation. In another report, transcriptional silencing of the endogenous CACTA transposon is relieved in fas mutants (Ono et al, 2006), although this transcriptional activation was relatively weak, infrequent, and stochastic. We have found that transcriptional activation of a set of euchromatin genes is not due to global changes in chromatin organization over large chromosomal regions.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified other DNA replication-related proteins involved in mediating TGS, including BRU1 (Takeda et al, 2004), chromatin assembly factor (CAF-1) subunits FAS1 and FAS2 (Ono et al, 2006;Schonrock et al, 2006), and TEBICHI (Inagaki et al, 2009). The release of TGS by defects in the DNA-replication machinery suggests that these processes must have a common mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…CAF1 seems to be necessary to ensure the stable inheritance and maintenance of epigenetic states during DNA replication (Kaya et al, 2001). Indeed, fas1 mutants display a stochastic release of Transcriptional Gene Silencing (TGS) and overexpression of genes located in heterochromatic genomic regions (Ono et al, 2006). In addition, the expression of stem-cell regulatory genes such as WUS is severely altered (Figure 1; Kaya et al, 2001).…”
Section: Chromatin Modification Events Required To Establish and Mainmentioning
confidence: 99%
“…This is the case of mutants altered in the Chromatin-Assembly Factor-1 (CAF1), a histone-binding protein complex which participates in de novo nucleosome assembly during DNA replication (Ramírez-Parra and Gutiérrez, 2007). CAF1 is formed by three subunits conserved in all eukaryotes that in Arabidopsis are encoded by FASCIATA1 (FAS1), FAS2 and MULTICOPY SUPPRESSOR OF IRA1 (MSI1) (Kaya et al, 2001;Hennig et al, 2003;Kirik et al, 2006;Ono et al, 2006). CAF1 seems to be necessary to ensure the stable inheritance and maintenance of epigenetic states during DNA replication (Kaya et al, 2001).…”
Section: Chromatin Modification Events Required To Establish and Mainmentioning
confidence: 99%